(untitled) (Web of Teachers: Inderscience Research, 2024)
In the realm of English as a Foreign Language (EFL) instruction, integrating technology into task-based approaches offers promising avenues for enhancing students’ reproductive skills. This article explores the rationale behind incorporating technology into task-based instruction and investigates its potential benefits and drawbacks. Drawing upon existing literature, this paper delves into the various ways technology can be seamlessly integrated into task-based activities to facilitate language learning. Additionally, it scrutinizes the advantages and disadvantages of this integration, providing insights into optimizing its efficacy. Ultimately, this article underscores the importance of judiciously leveraging technology within task-based instruction to nurture the reproductive skills of EFL students.